„Nihil Sine Deo” in Far-Right Protests: Ceremonial Revolutions During Anti-Vaccine Protests in Romania - Chiruta, Ionut (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2022)
This study investigates the far-right counter-hegemonic discourses employed in Romania during the Covid-19 vaccine roll-out and the promotion of green certificates. Using an array of traditional and occult symbols as well as religious iconography, the protests held by the Alliance for the Union of Romanians (AUR) employed ritualistic ceremonies and espoused counter-hegemonic discourses that confronted the authorities’ with the extreme religio-nationalist idea of “Romanianness”.
il., 24 cm
Keywords: ethnography -- journal; far-right; protests; counter-hegemony; ceremonial revolutions; Romania